Acquisition of English articles by L1 Chinese and L1 Malay ESL learners - Quek, Soh Theng (2018)
It is essential for native or first language (L1) speakers of article-less languages like Malay language and Mandarin Chinese to master the usage of English articles in order to be competent second language (L2) learners. Thus far, many studies have shown that L1 Malay and L1 Chinese ESL learners’ inability to grasp the usage of determiners as one of the main causes of unsuccessful acquisition of English in Malaysia. However, limited research has been conducted to address the article acquisition problem in particular hence no consensus has been achieved on how to tackle this problem among the Malaysian ESL learners. Grounded on the Bickerton’s Semantic Wheel Model for Noun Phrases (1981) and Ionin et al.’s Fluctuation Hypothesis (2004, 2008), L2 learners’ access to Universal Grammar in setting the correct parameters to acquire the Article Choice Parameter was investigated. The study employed a descriptive, ex-post facto and comparative cross-linguistic quantitative design to determine and compare the level of article acquisition of ESL learners. This study was also conducted to examine the influence and role of semantic features and L1 transfer in the acquisition of English articles by adult Chinese-speaking and Malay-speaking ESL learners with first languages without articles. Seventy-seven (77) L1 Chinese and 116 L1 Malay adult ESL learners at three levels of proficiency, elementary, intermediate and advanced, enrolled in three teacher training institutes were chosen to participate in the study. The participants completed a fill-in-the-article test, a forced-choice elicitation task, a forced-choice written elicited production task, and a picture-based comprehension task. Using Huebner’s (1983) classification system, the statistical analyses of the participants’ performance revealed that: (i) L1 Chinese and L1 Malay ESL learners showed similar path of article acquisition despite differences in L1s; (ii) all the six groups of the L1 Chinese and L1 Malay scored the highest mean percentages in the Type 4 context type; (iii) the ESL learners’ accuracy rates on article usage improved with increased proficiency level. Based on the predictions of Fluctuation Hypothesis and Article Choice Parameter, it was found that: (i) all the three proficiency groups of the L1 Chinese and L1 Malay learners were aware of the definiteness-based of English articles and showed fluctuation patterns in their article choice; (ii) definiteness and specificity had significant effect on the use of a and the among the L1 Malay learners; (iii) definiteness and specificity had significant effect on the use of the but only definiteness registered significant effect on the use of a among the L1 Chinese learners; (iv) only the advanced and intermediate groups of both L1 Chinese and L1 Malay ESL learners exhibited clear distinctions between the use of the in the two ‘unique’ categories and that in the ‘non-unique’ categories; and (v) the advanced and intermediate L1 Chinese and L1 Malay ESL learners showed their awareness in the discourse differences between the plural demonstrative and definites through the use of those and the. The L1 Chinese learners’ high accuracy rates in the indefinite contexts across the three proficiency groups highlighted the role of L1 lexical transfer and implied that the numeral one yi has been fully grammaticalized into an indefinite article whereas the numeral one satu or se in Malay Language is halfway towards the grammaticalization into an indefinite article. The findings of this study have pedagogical implications including classroom strategies used for the teaching and learning of the English articles, and point to problematic areas that may be encountered by ESL learners as a result of L1 transfer or fluctuation in their interlanguage. Thus, the findings of the study will contribute to the literature in the field of SLA particularly in the Malaysian context.